Ethnicity and Crime in the Netherlands - Unnever, James D. (International criminal justice review, 2019)
The research on the relationship between immigration and crime is central to the debate on immigration policies throughout Europe. This article reviews the research on whether immigrants in the Netherlands are more likely to engage in crime with a specific focus on whether Moroccans have a greater propensity to offend than the native Dutch. It is concluded that deficiencies in the research including the potential effects of bias against immigrant groups render the assessment of whether immigrants commit more crime than the native Dutch problematic.